2016
DOI: 10.1097/md.0000000000003425
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Infancy Weight Gain and 7- to 9-year Childhood Obesity Risk

Abstract: Obesity is increasing in developing countries. This study aimed to identify the association between rapid infancy weight gain and obesity risk among early school-age children.A total of 581 singletons (349 boys, 232 girls) whose mothers participated in an antenatal multiple micronutrient supplement trial in rural western China were followed from birth to between 7 and 9 years of age. Height and weight were measured at birth, 1.5 years, and between 7 and 9 years. At the 7- to 9-year time point, body composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 46 publications
0
40
0
1
Order By: Relevance
“…Infant rapid weight gain and later adiposity M. Zheng et al 323 obesity reviews countries from five continents: Europe (24,25,30,31), USA (32-34), Asia (26,(35)(36)(37)(38)(39), Australia (28,40), Brazil (29) and South Africa (27) with sample size ranging from 142 to 18,296 participants ( Table 1). Of the 12 prospective cohort studies, most studies included healthy term or appropriate-for-gestational age (AGA) children with no restrictions on birth weight status, and the subsequent adiposity outcomes were measured at ages 2 to 46.5 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Infant rapid weight gain and later adiposity M. Zheng et al 323 obesity reviews countries from five continents: Europe (24,25,30,31), USA (32-34), Asia (26,(35)(36)(37)(38)(39), Australia (28,40), Brazil (29) and South Africa (27) with sample size ranging from 142 to 18,296 participants ( Table 1). Of the 12 prospective cohort studies, most studies included healthy term or appropriate-for-gestational age (AGA) children with no restrictions on birth weight status, and the subsequent adiposity outcomes were measured at ages 2 to 46.5 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The case-control study included overweight/obese (cases) and normal weight (control) 3-to 5-year-old children born >37 weeks of gestation (37). The duration of RWG examined varied across studies, from birth to 3-4 months (26,35), birth to 6 months (29,40), birth to 1 year (27,28,31), birth to 18 months (36,38,39), and birth to 2 years (30,32,37). Two studies examined multiple periods of RWG from birth (33,34).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased birth weight was associated with childhood obesity (38,44,54,58,103,109,113,145,195,196,200), particularly birthweights >85th and >90th percentiles (56,144) and birthweights 2.5 kg (104), 3 kg (77), 3.5 kg (107,143,201,202), 4 kg (73,92,183,194,206), and >4.5 kg (159). In addition, studies identified rapid weight gain in the first year of life (109,158,168,187,188,199) as well as high infant weight (147,151,155,156,179) as risk factors.…”
Section: Weightmentioning
confidence: 99%